ミズホ カンソク キョテン ニオケル スイジョウキ リョウ カンソク - 西尾, 文彦; ニシオ, フミヒコ; NISHIO, Fumihiko (国立極地研究所, 1978)
P(論文) 1976年11月30日から1977年1月21日まで,みずほ観測拠点において水蒸気量の測定を行った.測定期間中,相対湿度は30～80%の値を示し,低気圧の影響を受けている期間は,斜面下降風に支配されている気象状況のときよりも高い相対湿度が観測された.水蒸気量が測定された気温範囲は,-6.5℃から-22.8℃であった.水蒸気量の測定結果から,この測定期間中の雪面からの昇華量が計算された.計算結果は雪尺測定による消耗量の2～3倍になった. The measurement of air humidity at the height of 1.5 meters above the snow surface was made at Mizuho Camp, East Antarctica, several times a day during the summer in 1976-1977, with the Karl Fisher method and the Assmann ventilated psychrometer method. The values of air humidity obtained by these two methods agreed within approximately 5% error. Water vapor pressure was estimated from the air humidity at temperatures between -6.5 and -22.8℃. The water vapor pressure obtained showed daily variation similar to air temperature. During the measurement no supersaturation of water vapor with respect to ice was detected and no ice fog was observed. The relative air humidity was between 30 and 80%. It was lower under a condition of predominant katabatic winds than under an influence of cyclones. The daily mean amount of sublimation estimated from the water vapor pressure obtained was between 1.3 and 1.9 millimeters per day and it was nearly two or three times larger than the amount of sublimation obtained by a direct measurement, snow stake measurement. departmental bulletin paper